Model fisik Kincir Air Untuk Irigasi Pertanian - Vicky, M Taufiq; Rinaldi, Rinaldi; Hendri, Andy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Physical model research of water wheel for agricultural irrigation is executed at Hidrotechnic’s Laboratory University of Riau. Model that is utilized doesn't utilize model scale, but phenomenon of prototype will be represented by model that made. Water wheel bases executed field study previous, having alone uniqueness. Paddle wheel lap speed one every minute (RPM) and debit who can be lifted by waters jacking tube visual's are relative stable. Even so was known it must be water wheel condition be still get improved debit that can be lifted by waters jacking tube. Water wheel model is undershoot water wheel made bases prototype aught at the site or at agricultural location. This waterwheel is made at Technicals Engineering Material Laboratory. This Waterwheel model specification with diameter 55 cm, broad 6 cm, long fan 6 cm, total fan 18 numbers and heavy 1,764 kg. The research did by variated foots up and tube dimension so gotten by water wheel model with tubed optimal one. Variation of tube is 3, 6, 9 and 18 numbers with each volume saves 3,4 ml, 8,0 ml, and 16,8 ml whereas debit flows are not variated.Result of this experiment showing that Waterwheel speed regarde by flow speed that punches waterwheel fans, but relationship both is not linear. Total tube and tube volume regard paddle wheel lap. Diameter 0,8 cm tube can’t lift waters because the diameter of tube are too small but diameter 1,3 cm and 1,7 cm tube both can lift flows.Maximum debits which diameter 1,3 tube can be lifted by jacking tube is 6,39 ml/dt, it happens upon tube amount 18 numbers whereas on diameter tube 1,7 cm maximum debits is 5,38 ml / dt happens upon tubed amount 6 numbers.Keywords: Model, Waterwheel, Undershot